Individuals' reasons for becoming substance addict according to social perspective: a quantitative study - Erkoç, Beyza; Avçin, Emel; Danış, Mehmet Zafer (Journal of Dependence, 2021)
Objective: This study aimed to determine the reasons for individuals to be addicted to substances based on the social perspective and to reveal whether the results vary according to demographic characteristics.Method: The study data were obtained from 416 individuals between 18 and 65 who lived in Yalova between 01.10.2020 and 30.11.2020. Data were collected with the support of researchers and pollsters.Results: The 3- dimensions construct validity of the questionnaire form used to determine the perspective of the society on substance addiction was achieved. These dimensions were named as family, socio-cultural environment, and near-distant environment. The final questionnaire form, consisting of 18 questions, is scored between 0 and 5. The scores of the participants from the final questionnaire form: the immediate environment factor (4 questions) score is 13.63±4.77, the family factor (7 questions) score is 24.58±7.21, and the socio-cultural factor (7 questions) score is 24.57±6.66.Conclusion: The three dimensions in the final questionnaire form are significant in terms of individuals being addicted to substances.
Keywords: Substance addiction; addiction; reasons for substance addiction